2022
DOI: 10.1002/app.52970
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing toughness of poly(lactic acid) by regulating the hydroxyl value and viscosity of hydroxyl terminated polybutadiene

Abstract: Brittleness of poly(lactic acid) (PLA), a biocompatible and biodegradable polymer obtained from renewable and natural sources, hinders its widespread applications. This study provides a convenient and economical way to enhance the toughness of PLA by using hydroxyl terminated polybutadiene (HTPB) liq-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…However, the presence of the liquid rubbers also increased the cold crystallization temperature ( T cc ) and broadened the corresponding peak, indicating lower crystallization rate of PLA. This behavior confirmed the effectiveness of the interfacial adhesion between the blend components, as also suggested in other studies reported in the literature 20,23–25 . The interaction /reaction between the functional groups in both components restricts the PLA chain mobility and consequently the chain packaging.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, the presence of the liquid rubbers also increased the cold crystallization temperature ( T cc ) and broadened the corresponding peak, indicating lower crystallization rate of PLA. This behavior confirmed the effectiveness of the interfacial adhesion between the blend components, as also suggested in other studies reported in the literature 20,23–25 . The interaction /reaction between the functional groups in both components restricts the PLA chain mobility and consequently the chain packaging.…”
Section: Resultssupporting
confidence: 89%
“…This behavior confirmed the effectiveness of the interfacial adhesion between the blend components, as also suggested in other studies reported in the literature. 20,[23][24][25] The interaction /reaction between the functional groups in both components restricts the PLA chain mobility and consequently the chain packaging.…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation